Quantitative provenance study of sediments in the coastal tidal flats of central Jiangsu based on grain-size End-Member analysis - Li, Yanxia; Zhao, Yifei; Xu, Wenjian; Liu, Nian; Xu, Min (Frontiers in Marine Science, 2023)
The coastal mudflats in central Jiangsu Province are influenced by the sediment supply from the Yangtze River and the abandoned Yellow River. However, the sources of sediment in this area have yet to be confirmed, and quantitative studies have been limited. In this study, we addressed this gap by obtaining sediment core samples with lengths of approximately 100 cm from Dongtai and Sheyang, respectively, on the central coast of Jiangsu Province in 2018. The sediment sources were identified and quantitatively evaluated using a grain-size end-member(EM) model. The findings revealed that (1) Sheyang was decomposed into five EMs, with EMs 1-3 originating from the abandoned Yellow River, EM 4 originating from the Yangtze River and the North Jiangsu radial sand ridges (NJRSR), and EM 5 originating from the NJRSR. Over a century scale, the abandoned Yellow River contributed 73.91% to sediment deposition in Sheyang, while the Yangtze River and the NJRSR contributed 26.09%. (2) Dongtai was decomposed into six EMs, with EMs 1-4 originating from the abandoned Yellow River, EM 5 originating from the Yangtze River, and EM 6 originating from the Yangtze River and the NJRSR. Over a century scale, the abandoned Yellow River contributed 70.55% to sediment deposition in Dongtai, and the Yangtze River and the NJRSR contributed 29.45%. (3) On a temporal scale, the contribution of the abandoned Yellow River to sediment deposition on the central mudflats of Jiangsu Province showed an increasing trend. Spatially, the contribution of the abandoned Yellow River to sediment deposition decreased from north to south. (4) There were significant changes in the sediment sources of Sheyang and Dongtai at the depths of 56 cm and 60 cm, respectively, which both experiencing an increased sediment supply from the abandoned Yellow River. In Dongtai, the sediment on the southern side had increased contributions from the abandoned Yellow River due to a reduction in the sediment supply from the Yangtze River. In Sheyang, the sediment on the northern side had increased contributions from the abandoned Yellow River due to the introduction of Spartina alterniflora, despite no actual changes in the sediment sources.